Comparison of Different Torque Calculation Methods in Direct Torque Control for Permanent-Magnet Synchronous Motors - Bozkurt, Ebubekir; Polat, Mehmet; Celik, Ibrahim (Institute of Electrical and Electronics Engineers Inc., 2024)
Permanent magnet synchronous motors (PMSM) are widely preferred because of their high efficiency and power-to-weight ratio. Today, it is used in various fields such as space and aviation technologies, electric vehicles, and elevators. Recently, direct torque control (DTC), a vector control method, has been effectively utilized in these motors. In this method, errors in torque calculations directly affect the system's stability. Ensuring the control stability of the system is a crucial issue. In this context, the control stability of the system can be improved by calculating the torque closer to the actual value. In PMSMs, the change in the load angle is directly linked to the change in torque. The torque changes with the load angle exhibit similar behaviors. In this study, the torque calculation of a PMSM is performed using the flux values calculated on different axes. The stator fluxes used in torque calculations are obtained on the d-q and x-y axis, respectively. These fluxes are put in the PMSM torque equation. It has been observed that the calculations performed on the x-y axis closely resemble the actual motor torque waveform. It has been put forward that these calculations have a positive impact on the stability of the system. © 2024 IEEE.
3rd IEEE International Conference on Electrical Power and Energy Systems, ICEPES 2024 -- 21 June 2024 through 22 June 2024 -- Bhopal -- 202357
Keywords: d-q currents; different torque calculation; load angle; PMSM